(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2022)
This study examined the role of debt management in resolving personal financial problems among two different groups (final- year students and employees) based on their gender. A convenience sampling approach by using a structured questionnaire as original data to obtain the primary data has been conducted. A total of 100 respondents has anticipated in completing the survey which consists of debt purpose, borrowing behaviour and money management skills. The data obtained was then analyzed by using descriptive, ANOVA and Pearson correlation which were processed using Statistical Package for Social Sciences (SPSS) software and Microsoft Excel. Before proceeding in data analysis, Cronbach’s Alpha and normality test have been conducted to check its validity and reliability of the questionnaire. The findings of the study reveal that debt management has a positive influence towards personal financing in self-control, overconfidence and money management skills. The findings signal the need to conduct more financial literacy program that promotes sustainable borrowing attitudes that is targeted at young adults to prepare them for viable personal finances in the future.